2019
DOI: 10.3390/mi10110716
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Coating Processed Phototransistors Enabled by Phase Separation of Semiconductor and Dielectric Blend Film

Abstract: Fabrication of organic thin-film transistors (OTFTs) via high throughput solution process routes have attracted extensive attention. Herein, we report a simple one-step coating method for vertical phase separation of the poly(3-hexylthiophene-2,5-diyl) (P3HT) and poly(methyl methacrylate) (PMMA) blends as semiconducting and dielectric layers in OTFTs. These OTFTs can be used as phototransistors for ultraviolet (UV) light detection, where the phototransistors exhibited great photosensitivity of 597.6 mA/W and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Wettability of the nanostructures surfaces was inspected by measuring the water contact angle and the obtained values are cited in Table 1 . Initial surface of P3HT is hydrophobic, in agreement with previous results reported in literature [ 64 ]. It has been previously reported that laser micro/nanostructuring and in particular LIPSS formation may provoke changes in the wettability of materials due to the morphological changes, to the chemical changes induced upon irradiation or to a combination of both factors.…”
Section: Resultssupporting
confidence: 92%
“…Wettability of the nanostructures surfaces was inspected by measuring the water contact angle and the obtained values are cited in Table 1 . Initial surface of P3HT is hydrophobic, in agreement with previous results reported in literature [ 64 ]. It has been previously reported that laser micro/nanostructuring and in particular LIPSS formation may provoke changes in the wettability of materials due to the morphological changes, to the chemical changes induced upon irradiation or to a combination of both factors.…”
Section: Resultssupporting
confidence: 92%
“… 21 The use of low-k PMMA as an insulating layer has been conventionally reported for P3HT thin-film transistors. 22 , 23 , 24 However, when utilizing a sole layer of PMMA as the gate dielectric, OTFT currents are not suitably regulated due to the poor insulating properties of PMMA. 25 , 26 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is known that binding polymers also have an effect on the device characteristics. [34][35][36][37] Here, it was found that the nature of the binding polymer influences the trap density of majority and minority charge carriers. The best OFET performance is found in the blend films exhibiting a lower level of traps, while the worst performance is encountered in the films with a higher level of majority charge carrier traps.…”
Section: Introductionmentioning
confidence: 99%